An introduction to Confucianism - Yao, Xinzhong (New York : Cambridge University Press, 2000)
Taking into account the history and range of Confucian Studies, this book introduces Confucianism - initiated in China by Confucius (551 BC-479 BC) - primarily as a philosophical and religious tradition. It draws together the many strands of Confucianism in a style accessible to students, teachers, and general readers.
Introduction : Confucian studies East and West -- 1. Confucianism, Confucius and Confucian classics -- 2. Evolution and transformation : a historical perspective -- 3. The way of Confucianism -- 4. Ritual and religious practice -- 5. Confucianism and its modern relevance.
Added t.p. title in Chinese characters.
Includes bibliographical references (pages 287-308) and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Confucianism; RELIGION -- Confucianism; Confucianism; Humaniora -- Filosofi; Electronic books